2017
DOI: 10.1136/bjophthalmol-2017-310476
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optical coherence tomography angiographic findings in Alzheimer’s type dementia

Abstract: In patients with ATD, retinal and choroidal vascular pathologies detected through OCTA imaging can be used as a new biomarker in the early diagnosis of the disease, follow-up of its progression and in investigating the efficacy of the drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
279
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(298 citation statements)
references
References 25 publications
11
279
4
4
Order By: Relevance
“…Using OCTA, Bulut et al showed that the superficial capillary plexus (SCP) vessel density (VD) was lower in AD compared to controls, and there was an association between the Mini Mental State Examination score and both SCP VD and foveal avascular zone (FAZ) area. 5 Kwapong et al showed similar changes in the early stages of PD compared to controls. 6 This suggests that retinal capillary impairment may occur early in the PD cascade before clinically apparent motor disorders manifest.…”
Section: Is Oct Angiography Useful In Neurodegenerative Diseases?mentioning
confidence: 90%
“…Using OCTA, Bulut et al showed that the superficial capillary plexus (SCP) vessel density (VD) was lower in AD compared to controls, and there was an association between the Mini Mental State Examination score and both SCP VD and foveal avascular zone (FAZ) area. 5 Kwapong et al showed similar changes in the early stages of PD compared to controls. 6 This suggests that retinal capillary impairment may occur early in the PD cascade before clinically apparent motor disorders manifest.…”
Section: Is Oct Angiography Useful In Neurodegenerative Diseases?mentioning
confidence: 90%
“…In addition, these early microvascular changes detected using OCT-A in diabetic eyes without DR are not very specific findings. For example, patients with other retinal diseases (e.g., AMD 12 and retinal vascular occlusion 13 ) and patients with neurodegenerative disease (e.g., Alzheimer's disease 14 and Parkinson's disease 15 ) also demonstrate nonspecific microvascular alterations in their macula, similar to those observed with DR. Therefore, the clinical relevance of microvascular changes preceding retinopathy should be established before these changes can be used as novel retinal biomarkers for DR in practice.…”
mentioning
confidence: 94%
“…Bulut et al were probably the rst to use OCTA imaging to analyze vascular lesions of the retina in AD patients. They found a reduction in the density of vessels in SVP in the eyes of AD compared to HC [18]. Subsequent research groups con rmed a decrease in retinal vascular density in SVP in patients diagnosed with AD [46][47][48].…”
Section: Discussionmentioning
confidence: 95%
“…This is probably due to the diameter of the vessels: DVP vessels are thinner and have a smaller cross-section making them more sensitive to disease progression. Furthermore, Aβ plaques accumulating around the walls of vessels reduce the diameter of vessels leading to blood ow disorders, and also reduced angiogenesis, likely due to binding and blocking of vascular endothelial growth factor by Aβ deposits [18,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation